Determinants of Functional Outcome in Distal Radius Fractures in High-Functioning Patients Older Than 55 Years. Issue 8 (August 2016) - Larouche, Jeremie; Pike, Jeffrey; Slobogean, Gerard P.; Guy, Pierre; Broekhuyse, Henry; O'Brien, Peter; Lefaivre, Kelly A.
Abstract : Objectives: To determine the influence of treatment and radiographic parameters on patient-reported functional outcomes on a population of non-frail elderly with distal radius fractures. Design: Prospective cohort study. Setting: Level 1 trauma center. Patients/Participants: Patients older than 55 years presenting with a distal radius fracture and a Canadian Study of Health and Aging Clinical Frailty Scale score of 1 or 2. Intervention: Closed reduction and casting or open reduction and internal fixation as per the treating surgeons' decision. Main Outcome Measures: Radiographic scores at baseline, 6 weeks, and 12 weeks, as well as Disabilities of the Arm, Shoulder and Hand, Short Form 36, and Patient-Reported Wrist Evaluation scores up to 1 year after injury. Univariate analysis and linear regression analysis were performed on outcome measures. Results: No difference exists in outcomes based on treatment choice. Patients with ulnar positivity greater than 2 mm at baseline, after treatment, and at final follow-up had worse patient-reported scores at 1 year. Persistent articular gaps and/or steps greater than 2 mm after treatment were also associated with worse patient-reported outcomes. Conclusion: Even in high-functioning patients older than 55 years, there was no difference in patient-reported outcomes at 1 year in the open reduction group as compared with the closed reduction group. Instead, physicians should pay particular attention to radial shortening and persistent articular gaps following their chosen treatment plan for distal radial fractures. Level of Evidence: Prognostic Level I. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.